Paradigma Mutu Prespektif Al-Quran Dan Filosofi Mutu Menurut Fred Smith, W. Edward Deming, Michael Sallis, Joseph Juran - Septi Ayana, Riya; Dakir (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2025)
This study aims to analyze and compare quality concepts from the Qur'an and quality management experts such as Frederick W. Smith, W. Edwards Deming, Michael Sallis, and Joseph Juran. The research highlights that, although originating from different contexts, both perspectives emphasize continuous improvement, holistic quality, and commitment to excellence. In the Qur'an, quality is closely related to the principle of ihsan—doing good and striving for the best in all aspects, including work, worship, and social interactions, integrating moral, spiritual, and social dimensions. Meanwhile, the quality philosophies of the experts focus on systematic processes, customer satisfaction, and organizational involvement. This study employs a library research method to systematically review relevant literature and extract core principles from both sources. The findings reveal that integrating Qur'anic values with modern quality management philosophies offers a comprehensive framework that can enhance individual and organizational performance, especially in educational and industrial sectors. This integration supports the development of ethical, competent, and competitive individuals and institutions. The study contributes to the discourse on quality management by bridging spiritual and contemporary approaches, offering practical implications for implementing quality improvements in diverse settings.